2017
DOI: 10.1021/acs.jafc.6b05103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in Vitro Gastrointestinal Digestion on Encapsulated and Nonencapsulated Phenolic Compounds of Carob (Ceratonia siliqua L.) Pulp Extracts and Their Antioxidant Capacity

Abstract: To determine the effect of in vitro gastrointestinal digestion on the release and antioxidant capacity of encapsulated and nonencapsulated phenolics carob pulp extracts, unripe and ripe carob pulp extracts were microencapsulated with polycaprolactone via double emulsion/solvent evaporation technique. Microcapsules' characterization was performed using scanning electron microscopy and Fourier transform infrared spectrometry analysis. Total phenolics and flavonoids content and antioxidant activities (ORAC, DPPH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 36 publications
7
72
0
1
Order By: Relevance
“…In accordance with the present study, several previous works also reported a decrease in TFC after gastrointestinal digestion. Pellegrini et al found that the TFC of five quinoa seeds was negatively affected by the intestinal phase, whereas Ydjedd et al demonstrated that simulated intestinal conditions decreased the TFC of encapsulated and non‐encapsulated carob pulp extracts …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the present study, several previous works also reported a decrease in TFC after gastrointestinal digestion. Pellegrini et al found that the TFC of five quinoa seeds was negatively affected by the intestinal phase, whereas Ydjedd et al demonstrated that simulated intestinal conditions decreased the TFC of encapsulated and non‐encapsulated carob pulp extracts …”
Section: Resultsmentioning
confidence: 99%
“…Pellegrini et al found that the TFC of five quinoa seeds was negatively affected by the intestinal phase, whereas Ydjedd et al demonstrated that simulated intestinal conditions decreased the TFC of encapsulated and non-encapsulated carob pulp extracts. 3,28 Validation of applied HPLC method HPLC is a very effective and versatile chromatographic technique for the detection and quantification or general profiling of phenolics in food matrices. In this study, an HPLC method was developed using ten phenolics as references and further validated for linearity, sensitivity, LOD and LOQ, accuracy and precision.…”
Section: Discussionmentioning
confidence: 99%
“…The sugar moiety attached to flavonol did not significantly affect the recovery, as it was previously observed by Ortega et al [ 39 ] who obtained recoveries of 51.5% and 44.2% for myricetin-rhamnoside and myricetin-glucoside respectively, after a simulated digestion process. Likewise, Ydjedd et al [ 40 ] reported that after intestinal digestion quercetin rhamnoside and myricetin rhamnoside showed recoveries of 47.9% and 40.2%, respectively. Moreover, glycosylation plays a protective role during the digestion process.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of in vitro gastrointestinal digestion on phenolic compounds has been studied in numerous fruit such as apple (BOUAYED et al, 2011), fig (KAMILOGLU & CAPANOGLU, 2013, blueberry (CORREA-BETANZO et al, 2014), strawberry grape (GRANESE et al, 2014), pomegranate (GULLON et al, 2015), and carob (YDJEDD et al, 2017). Nevertheless, to our knowledge, there is only one study regarding the intestinal bioaccessibility of polyphenols and antioxidant capacity of pulp and seeds of cactus pear, which is the investigation of REZ-MORENO and co-workers (2011).…”
Section: Acta Alimentaria 47 2018mentioning
confidence: 99%